RECONCEPTUALIZING MANAGERIAL LEADERSHIP IN EDUCATION: A TERMINOLOGICAL AND EPISTEMIC REVIEW OF CONTEMPORARY LEADERSHIP RESEARCH - Katrunnida; Nurlaila; Istiarsyah (Yayasan Sukma, 2026)
Managerial leadership has remained a prominent construct in contemporary educational leadership research; however, its conceptual foundations continue to exhibit significant ambiguity. This study reconceptualizes managerial leadership in education through a terminological and epistemic systematic review of leadership literature published between 2003 and 2022. Rather than assessing leadership effectiveness, the review critically examines how managerial leadership is defined, extended, substituted, and progressively diluted across key sections of academic articles. Employing a structured content analysis framework, the study identifies four recurring epistemic patterns: conceptual stability, conceptual extension, conceptual substitution, and conceptual drift. The findings reveal that despite sustained scholarly attention, terminological inconsistency and unexamined conceptual extensions persist, particularly in discussion and conclusion sections, resulting in epistemic fragmentation and weakened theoretical coherence. To address these challenges, the study advances an integrative epistemic reconceptualization framework that explicates how terminological inconsistency emerges and how epistemic discipline can restore conceptual clarity and cumulative knowledge building. By foregrounding terminological accountability and epistemic coherence, this study contributes a refined conceptual lens for strengthening theory development, enhancing research synthesis, and advancing more coherent future scholarship on managerial leadership in education.